Monitoring soil slope of tropical residual soil by using tree water uptake method - Zaini, M.S.I.; Mohd Fakhrurrazi, Ishak; Muhammad Farhan, Zolkepli (IOP Publishing, 2020)
From years to years, the construction of residential buildings at hill-site in Malaysia will lead to various fatalities event. Cutting down of trees can vanish the reinforcement provided by the root of tree to the soil by means of weakening the soil shear strength due to the increasing value of pore water pressure and decreasing value of effective stress. Root of a tree plays an important part in preventing landslides event to occur either it is by modifying the soil moisture regime via evapotranspiration or providing root reinforcement within the soils. Water uptake by plant roots is fundamental in many applications agriculture. This study is conducted to explores the vegetation approach by using tropical mature tree and monitors the activeness of the root zone of a tree that lies at the top of the slope by which the data of the matric suction generated within this section of the slope is recorded by using Tensiometer and applied to the slope stability problem to increase the value of factor of safety (FOS). Based on the research conducted, it is proven that by using tree water uptake method can increase the FOS of the slope up to 57%. In retrospect, the method used in preventing the landslides event to occur at the slope is economical and eco-friendly which can be implemented globally as this is the most nature method to prevent landslide and required low cost compared to other methods.